2007
DOI: 10.1007/s12038-007-0072-6
|View full text |Cite
|
Sign up to set email alerts
|

Selenium acts as an insulin-like molecule for the down-regulation of diabetic symptoms via endoplasmic reticulum stress and insulin signalling proteins in diabetes-induced non-obese diabetic mice

Abstract: To investigate whether selenium (Sel) treatment would impact on the onset of diabetes,we examined serum biochemical components including glucose and insulin,endoplasmic reticulum (ER) stress and insulin signalling proteins, hepatic C/EBP-homologous protein (CHOP) expression and DNA fragmentation in diabetic and non- diabetic conditions of non-obese diabetic (NOD) mice. We conclude that (i) Sel treatment induced insulin-like effects in lowering serum glucose level in Sel-treated NOD mice, (ii) Sel-treated mice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 50 publications
0
29
0
Order By: Relevance
“…Selenium has been proved to have a role in prevention of cancer [66], provide optimal endocrine and immune function, and moderate the inflammatory response [35,67]. Selenium had been proven to act as an insulin mimetic by activating key selenoproteins involved in the insulin-signal cascade [68][69][70].…”
Section: Discussionmentioning
confidence: 99%
“…Selenium has been proved to have a role in prevention of cancer [66], provide optimal endocrine and immune function, and moderate the inflammatory response [35,67]. Selenium had been proven to act as an insulin mimetic by activating key selenoproteins involved in the insulin-signal cascade [68][69][70].…”
Section: Discussionmentioning
confidence: 99%
“…Animal model work has also suggested a role for selenium supplementation in reducing some biochemical effects of diabetes. Hwang et al (176) found that selenium supplementation of NOD (nonobese diabetic mice) counteracted ER stress through stimulation of PERKeIF2 and IRE1-JNK pathways and also activating the insulinsignalling pathway. The study also suggested that treatment with selenium may influence aspects of other chronic diseases associated with diabetes, for example, by decreasing the levels of serum markers of liver damage.…”
Section: Diabetesmentioning
confidence: 99%
“…In a study using NOD mice, elevated serum enzymes associated with liver damage and apoptosis, as indicated by marked DNA fragmentation were observed and all these changes were decreased with selenium treatment [23]. The BB/WOR diabetic rat is another Type 1 diabetes animal model which has been used extensively to study the effects of hyperglycemia induced injury.…”
Section: Hyperglycemia Induced Changes In Liver In Animal Modelsmentioning
confidence: 99%